A retrospective chart review to assess the impact of alpha-guided transcranial magnetic stimulation on symptoms of PTSD and depression in active-duty special operations service members - Bailar-Heath, Marybeth; Burke, Riley; Thomas, Delisha; Morrow, Chad D. (Frontiers in Psychiatry, 2024)
Introduction Special Operations Forces service members (SOF) are regularly exposed to traumatic and concussive events, increasing the prevalence of symptoms of post-traumatic stress disorder (PTSD) and depression, shortening potential years of service. Methods This retrospective chart review presents preliminary data on a Human Performance Optimization (HPO) program that provided an average of 30 sessions of individualized alpha frequency repetitive transcranial magnetic stimulation (α-rTMS) to active-duty SOF as to reduce symptoms of PTSD and depression following traumatic brain injury. Scores from the PTSD Checklist for DSM-5, PROMIS Depression short form and Perceived Deficits Questionnaire (PDQ) were reviewed. Results Significant reductions were noted after the HPO program in all clinical scales with an average 37% decrease in PCL-5 (p<.01), 11.3% reduction in PROMIS depression T-scores (p<.01), and 45.5% reduction in PDQ scales by session 30 (p<.01), with side effects matching those commonly reported in rTMS. Importantly, the average PCL-5 score decreased from 42.9 to 27 by end of the treatment program, which is below the clinical threshold of 33 for presence of PTSD. For those with depression symptoms scores greater than cut off clinical thresholds at baseline, 46% resolved following treatment. Conclusion This data provides preliminary support for safe application of α-rTMS for symptom reduction in active-duty special operations military personnel.